2005
DOI: 10.1128/iai.73.12.8209-8218.2005
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilumDelay of Neutrophil Apoptosis through the p38 Mitogen-Activated Protein Kinase Signal Pathway

Abstract: Human granulocytic anaplasmosis is caused by the obligate intracellular bacterium Anaplasma phagocytophilum. The bacterium avoids host innate defenses in part by infecting, surviving in, and propagating in neutrophils, as well as by inhibiting neutrophil apoptosis. However, the mechanisms of A. phagocytophilum survival in neutrophils and the inhibition of spontaneous apoptosis are not well understood. In this study, we demonstrated that antiapoptotic Mcl-1 protein (Bcl-2 family) expression is maintained and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 55 publications
2
70
3
Order By: Relevance
“…These results suggest that the intrinsic mitochondrial pathway, including Mcl-1 and caspase-3, is involved in the delay of neutrophil apoptosis induced by T. vaginalis lysate. These results also correspond with the results of other studies which reported that Anaplasma phagocytophilum delayed neutrophil apoptosis via Mcl-1 and caspase-3 mechanisms [9]. Taken together, our results indicate that lysate of the human trichomonad, T. vaginalis, delayed human neutrophil apoptosis through inhibition of typical features of apoptosis such as decreased MMP, caspase-3 activation, and reduction of Mcl-1.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results suggest that the intrinsic mitochondrial pathway, including Mcl-1 and caspase-3, is involved in the delay of neutrophil apoptosis induced by T. vaginalis lysate. These results also correspond with the results of other studies which reported that Anaplasma phagocytophilum delayed neutrophil apoptosis via Mcl-1 and caspase-3 mechanisms [9]. Taken together, our results indicate that lysate of the human trichomonad, T. vaginalis, delayed human neutrophil apoptosis through inhibition of typical features of apoptosis such as decreased MMP, caspase-3 activation, and reduction of Mcl-1.…”
Section: Discussionsupporting
confidence: 82%
“…For example, trichomonads caused neutrophils to produce low levels of IL-8 compared to live T. vaginalis, and IL-8 may contribute to apoptotic changes of neutrophils [5]. IL-8 secretion was also observed with bacterial supernatant or Anaplasma phagocytophilum treated neutrophils, and apoptosis delay was also shown in these neutrophils [9,21]. Accordingly, it is suggested that a balance of viable trophozoites, lysates, and ESP form T. vaginalis may contribute to progression of inflammatory reactions in trichomoniasis via the control of neutrophil apoptosis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A. phagocytophilum replicates in the parasitophorous vacuole of neutrophil granulocytes and forms microcolonies called morulae. Previous reports show that infection with A. phagocytophilum delays neutrophil apoptosis by upregulating the p38 mitogen-activated protein kinase (MAPK) pathway (10) and by modulating extrinsic and intrinsic pathways of apoptosis (21). The phosphatidylinositol 3-kinase (PI3K)/Akt and NF-B pathways are considered as important survival signaling pathways in neutrophils (54).…”
mentioning
confidence: 99%
“…In the circulation, neutrophils have a short life span: they undergo spontaneous apoptosis within 6 to 10 h. However, neutrophil apoptosis is delayed after exposure to proinflammatory stimuli such as interleukin-8 (IL-8), tumor necrosis factor alpha (TNF-␣), IL-1, IL-2, gamma interferon (IFN-␥), granulocyte-macrophage colony-stimulating factor (GM-CSF), G-CSF, or lipopolysaccharide (LPS) (3,25,28,39). In addition, several intracellular pathogens such as Anaplasma phagocytophilum, Leishmania major, Chlamydia pneumoniae, and respiratory syncytial virus have developed strategies to manipulate the spontaneous apoptosis of host neutrophils (1,10,47).…”
mentioning
confidence: 99%